International Youth Development: A Review of Youth – Realities and Challenges for Achieving Development with Equality - Tegan Walker (Journal of International Agricultural and Extension Education, 2019)
Youth: Realities and Challenges for Achieving Development with Equality” edited by Daniela Trucco and Heidi Ullmann contributes to the call for stronger multidisciplinary approaches to policymaking related to youth in the Latin American and Caribbean region. The publishers, The Economic Commission for Latin America and the Caribbean, recognize equality as the ultimate aim of development and young people as essential change agents. Engaging youth in the development process is an essential step for creating an egalitarian society, respecting the rights and needs of youth, and creating comprehensive inclusive policies. Data over 13 years are presented from multiple reputable sources and examined by the editors through socioeconomic quintiles and living areas. The region of Latin American and the Caribbean is defined as inclusive of all Central and South American countries, Mexico, and all island nations and U.S. territories in the Caribbean. The editors defined youth as representing those aged between 15 and 29. The editors addressed the main challenges of development and inclusion faced by youth within Latin America. Six spheres are presented encompassing the social inclusion of youth: education, employment, health, violence, culture, and participation. Throughout the book the editors highlighted gaps in various sectors that lead to the social exclusion of youth. A disconnect was found between advances in education and the lack of available opportunities in the labor market. The region overall is reaching higher levels of education, however there are fewer work opportunities available. “Employment is the most pivotal link in the chain of social inclusion for young people” (Trucco & Ullmann, 2016, pp. 45-46). The disconnect between education advancements and employment opportunities continues to be an issue in the region.
Keywords: Latin America; social inclusion; Extension; youth programming; policy recommendations